The Metaverse in Engineering Management: Overview, Opportunities, Challenges, and Future Research Agenda - Ooi K.-B.; Tan G.W.-H.; Al-Emran M.; Al-Sharafi M.A.; Arpaci I.; Zaidan A.A.; Lee V.-H.; Wong L.-W.; Deveci M.; Iranmanesh M. (Institute of Electrical and Electronics Engineers Inc., 2025)
The metaverse is widely regarded as 'the evolution of the Internet,' with the potential to provide opportunities for various stakeholders. In addition to enhancing productivity among employees and creating new business models and revenue streams, it can increase the competitiveness of organizations. However, like any disruptive technology, it poses significant challenges, such as data privacy, security, and ethics. This study acknowledges the growing significance of the metaverse and provides valuable insights into five key areas from the viewpoint of engineering management: supply chain management, logistics management, decision-making, technology management, and knowledge management. Drawing on the contributions of ten experts from various disciplinary backgrounds, each area has an overview, opportunities, challenges, and research agenda. By combining these diverse perspectives through a multidisciplinary approach, this study makes significant contributions to both the academic and practical communities, particularly in the field of engineering management, including the management of technology and innovation. The insights presented can also be utilized to shape policies and drive social and economic progress in the emerging era of the metaverse. ? 1988-2012 IEEE.